Identifying criteria for prioritizing process transformation projects - Conte Costa Laurindo, Diego (2024)
Different processes exist within organizations and due to their particularities, which processes should be prioritized in improvement or transformation projects must be identified. Based on a literature review, this research raised 24 criteria for decision making in prioritizing processes in improvement and transformation projects. No indication of universal criteria which can be replicated in any and any organization has been identified in the literature. However, there was great relevance to strategic aspects of the organization. Among the most used criteria, strategic alignment, operating costs, financial return, innovation and quality stand out. All criteria were classified into 5 categories (strategy, financial, quality, impact on clients, and efficiency), then called macro criteria, and a generic hierarchical structure was proposed for multi-criteria decision making. In this generic structure, the criteria and macro criteria can be adapted by specialists or practitioners of the AHP (Analytic Hierarchy Process), according to the application environment, by selecting criteria and/or macro criteria, as well as also assigning specific weights to these criteria and sub-criteria according to judgments provided by the method, method the framework for another multi-criteria method.